1897 Neb. Laws 162 - (:unkn) unknown (My University, 1897)
Ch. 14, § 24, pt. 38: To . . . regulate and prevent the transportation of gun powder or other explosives or combustible articles, tar, pitch, rosin, coal, oil, benzine [sic], turpentine, hemp, cotton, nitroglycerine, dynamite, petroleum, or any other productions thereof and other materials of like nature[.]
Keywords: GUNPOWDER - TRANSPORTATION